English Proses Dramatisasi Pesan dalam Pembentukan Desa Miliader (Studi Pada Desa Wisata Sekapuk, Kecamatan Ujung Pangkah, Kabupaten Gresik) - Fuaddah, Zamroatul; Dwi Astuti Nurhaeni, Ismi; Noevi Rahmanto, Andre (Sodality: Jurnal Sosiologi Pedesaan, 2023)
Communication of disseminating stakeholder messages through dramatization aims to improve the economy and people's welfare. This article aims to examine how symbolic convergence in the tourism sector can create social change in the Selo Tirto Giri Tourism Object, Gresik Regency. This study uses the theory of symbolic convergence from Bormann and the theory of structuration from Gidden. This research method uses a qualitative descriptive method with a single case study. The informants of this research were village stakeholders who were determined purposively. Data validity uses source triangulation. Data analysis uses fantasy theme analysis where fantasy messages become the unit of analysis Lindlof and Taylor. The results of the study show that the dramatization of messages is created through fantasy themes, namely awareness of developing regions, getting along in harmony, and prosperous and independent communities. Symbolic convergence is related to the structuration that occurs symbolically in Sekapuk Village. The existence of repeated messages creates a dimension of public awareness that shapes the structure and creates social change. The process of dramatizing messages and structuring forms the tourist attraction of Selo Tirto Giri so that Sekapuk Village, which is a poor village, becomes a Millionaire Village.